ANALISIS TEKSTUAL GAYA BAHASA IKLAN HARBOLNAS VERSI SAKIT JIWA TOKO ONLINE BUKALAPAK.COM DI INTERNET - Wasono Adi (Communicology: Jurnal Ilmu Komunikasi, 2018)
ABSTRACT This paper aims to reveal the meaning of the style of the National Online Shopping Day advertising language or abbreviated as HARBOLNAS in 2016 BukaLapak.com online version of the mental illness with, textual analysis techniques from the ad text using the study of textual and contextual cohesion. The approach utilizes the concept of language style that focuses on grammatical aspects, words or groups of words that become references, substitutions, and ellipsis. It is seen that, the advertisement uses aspects of grammatical aspects in terms of references, substitutions, and ellipsis in the text that it uses to listen to the attention of its readers or prospective consumers. The discourse of the ad language is intentionally used even if it is not in accordance with the rules of language, this is more due to the efforts of the advertiser to provide information briefly and with an impact that can immediately affect the reader. Based on the above conclusions, it is recommended in the production of advertising texts to take advantage of the practice of language that has aesthetic values ​​to attract the interest of readers, the target audience of advertisements or prospective consumers. Keywords: Advertisements, Language Style, Grammatical Aspects ABSTRAK Makalah ini bertujuan untuk mengungkap makna gaya bahasa iklan Hari Belanja Online Nasional atau disingkat HARBOLNAS tahun 2016 toko online BukaLapak.com versi sakit jiwa dengan, teknik analisis tekstual dari teks iklan tersebut dengan memanfaatkan kajian kohesi tekstual dan kontekstual. Pendekatan memanfaatkan konsep gaya bahasa yang memfokuskan pada aspek-aspek gramatikal, kata-kata atau kelompok kata yang menjadi referensi, substitusi, dan ellipsis. Terlihat bahwa, iklan tersebut menggunakan aspek aspek gramatikal dalam hal referensi, substitusi, dan ellipsis dalam teks yang digunakannya untuk mearik perhatian pembacanya atau calon konsumen. Wacana bahasa iklan tersebut sengaja digunakan walaupun tidak sesuai dengan kaidah bahasa, hal ini lebih karena upaya dari pihak pengiklan untuk memberikan informasi secara singkat dan dengan dampak yang segera dapat mempengaruhi pembaca. Berdasarkan simpulan di atas direkomendasikan dalam produksi naskah iklan agar memanfaatkan praktik berbahasa yang memiliki nilai-nilai estetis untuk menarik minat pembaca, khalayak sasaran iklan atau calon konsumen. Kata Kunci: Iklan, Gaya Bahasa, Aspek Gramatikal